Pengaruh Motif, Lokasi dan Kualitas Layanan terhadap Keputusan Pemilihan Fitness Center (Studi pada Member Fitness Center Best Gym Malang) - Dian Yuli Prasetiyo (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Malang, 2016)
ABSTRACT: The purpose of this study is to determine: 1) the conditions of motive, location, quality of service and customer selection decision at the fitness center at Best gym members; 2) the effect the selection decision motif fitness center at Best gym members; 3) the effect of the location of the decision on the election of members of fitness centers Best gym; 4) the effect of the service quality of the decision on the election of members of fitness centers Best gym; 5) there are variable that becomes the dominant influence on the decision on the election of members of fitness centers Best Gym. The design used fot this study is descriptive correlational study. By using the slovin formula obtained a sample of 185 respondents. Sampling techniques used is simple random sampling. Analysis of data is done by using multiple regression analysis. The findings show that: 1) motive on Best Gym fitness center member Malang is high, the location of Best Gym fitness center located in a strategic area in Malang, and service quality is perceived good by fitness center members of Best Gym Malang; 2) there is a significant positive effect on the preference decision motive for fitness center at Best Gym member Malang; 3) there is a significant positive effect on the location selection decision fitness center at Best Gym member Malang; 4) there is a significant positive effect on the quality of the decision on the election of members of fitness centers Best Gym Malang; 5) there is dominant variables that influence the decision on the election of members of the fitness center Best gym. Keywords: motive, location, service quality, preference decisions ABSTRAK: Tujuan penelitian ini adalah untuk mengetahui: 1) kondisi motif, lokasi, kualitas layanan dan keputusan pemilihan konsumen pada fitness center pada member Best gym; 2) pengaruh motif terhadap keputusan pemilihan fitness center pada member Best gym; 3) pengaruh lokasi terhadap keputusan pemilihan fitness center pada member Best gym; 4) pengaruh kualitas layanan terhadap keputusan pemilihan fitness center pada member Best gym; 5) terdapat variabel yang berpengaruh dominan terhadap keputusan pemilihan fitness center pada member Best Gym. Rancangan penelitian menggunakan penelitian deskriptif korelasional. Rancangan penelitian menggunakan penelitian deskriptif korelasional. Dengan menggunakan rumus slovin diperoleh sampel sebanyak 185 responden. Tehnik pengambilan sampel dengan simple random sampling. Analisis data menggunakan analisis regresi berganda. Temuan penelitian menunjukkan: 1) motif pada member fitness center Best Gym Malang tinggi, lokasi fitness center Best Gym Malang strategis, dan kualitas layanan dipersepsikan baik oleh member fitness center Best Gym Malang; 2) terdapat pengaruh positif signifikan motif terhadap keputusan pemilihan fitness center pada member Best Gym Malang; 3) terdapat pengaruh positif signifikan lokasi terhadap keputusan pemilihan fitness center pada member Best Gym Malang; 4) terdapat pengaruh positif signifikan kualitas terhadap keputusan pemilihan fitness center pada member Best Gym Malang; 5) terdapat variabel yang pengaruhnya dominan terhadap keputusan pemilihan fitness center pada member dari Best gym. Kata kunci : motif, lokasi, kualitas layanan, keputusan pemilihan